Variations in radiographic appearance of articular cartilage of knee joints in persons of 35 to 65 years of age - Pulivarthi, Himani; Maddikunta, Vasantha; Rao, P. Koteswara (International Journal of Research in Medical Sciences, 2017)
Background:Osteoarthritis is a slowly progressive degenerative disease characterized by gradual loss of articular cartilage. Osteoarthritis is not a normal process of ageing processes. Age related changes are distinct from osteoarthritic changes but when coupled with certain precipitating factors like obesity, muscle weakness and neurological dysfunction may play an important role in the causation of osteoarthritis. Osteoarthritis occurrence appears to increase with patient’s age in a non-linear fashion. The prevalence of disease increases dramatically after the age of 50 years, likely because of age related alterations in collagen and proteoglycan synthesis coupled with diminished nutrient supply to the cartilage. Methods:In this paper presenting the naked eye assessment of radiographic appearance of articular cartilage of knee joints of 100 persons (both men and women) of 35 to 65 years of age with symptoms like pain and stiffness of the joint. Results:Parameters like changes in the joint space width, the presence or absence of osteophytes and subchondral sclerosis and cysts were noted. The correlation between the patient’s age, sex, symptoms and radiological appearance were observed. Conclusion:Osteoarthritis has a higher prevalence and more often generalized in women than in men. Before the age of 50 years, the incidence of osteoarthritis is low and men have a slightly higher prevalence than women, but after the age of 50 years, the disease becomes more frequent and women have a much higher prevalence with a female to male ration of about 12:1. The reason for this is sex difference in cartilage volume.